“Philosophy Chapters” of St. John of Damascus: an Overview on the Structure - Atanasov, Atanas (Forum Theologicum Sardicense, 2025)
Atanas Atanasov, “Philosophy chapters” of St. John of Damascus: an Overview on the Structure. The work "Philosophy Chapters," also known as "Dialectica," elaborates on a unique idea that is briefly outlined in the treatise "Elementary Introduction to Dogmas." It surpasses the Introduction not only in volume but also in its conception. The work is based on the premise that by separating and distributing the material within the Philosophical Chapters and Exposition—which, according to the tradition of the text, form a cohesive whole—a differentiation between philosophy and dogmatics can be achieved. This differentiation is crucial for the development of dogmatics as a science. The author compiles much of the material from sources that cannot be verified by modern research, aiming to systematize dogmatic teachings with a firm belief in the importance of logical definitions. His dialectical work results from a thorough consideration of dogmas. The detailed elaboration of logic, which in this respect resembles the comments of school philosophy, allows for a more speculative consideration of the dogmatic teachings themselves. This approach is evident in the small dogmatic treatises of St. John of Damascus.